Linear programming technique based optimal relay coordination in a radial distribution system - Nagesh Kumar, G. V.; Sravana Kumar, B.; Venkateswara Rao, B.; Sobhan, P. V. S.; Appala Naidu, K. (International Journal of Engineering and Technology, 2018)
Now-a-days to ensure power continuity and system’s reliability the protection system is to be designed properly for distribution systems to handle the faults to avoiding the damage to the equipments and to the service engineers. Different types of relays with different working principles are used to detect different types of faults in the system. In order to avoid mal operation of relays, proper coordination is to be carried out. The objective of this paper is to maintain the relay coordination as well as to decrease the working time of relays by optimizing the values of time dial setting (TDS) using linear programming problem technique (LPP). The inequality constraints guarantee the coordination margin for each primary or backup relay pairs having a fault very close to the primary relay. Simulation is carried out on a IEEE 15 bus balanced radial distribution system with 3 different types of relays namely standard inverse, extremely inverse and very inverse relay and the results are presented and analyzed.